Influence of polar stratospheric clouds on the depletion of Antarctic ozone - Salawitch, Ross J.; Wofsy, Steven C.; Mcelroy, Michael B. (1988)
Precipitation of nitrate in polar stratospheric clouds (PSCs) can provide a significant sink for Antarctic stratospheric odd nitrogen. It is argued that the depth of the Ozone Hole is sensitive to the occurrence of temperatures below about 196 K. An increase in the prevalence of temperatures below 196 K would enhance ozone loss by increasing the spatial extent and persistence of PSCs, and by decreasing the level of HNO3 that remains following PSC evaporation. Concentrations of halogen gases in the 1960s and earlier were insufficient to support major ozone loss, even if thermal conditions were favorable.